Construction of Porous Mo3P/Mo Nanobelts as Catalysts for Efficient Water Splitting. (4th October 2018) - Li, Feng; Han, Gao‐Feng; Noh, Hyuk‐Jun; Lu, Yalin; Xu, Jiao; Bu, Yunfei; Fu, Zhengping; Baek, Jong‐Beom
Abstract: A novel synthesis strategy is demonstrated to prepare Mo3 P/Mo nanobelts with porous structure for the first time. The growth and formation mechanism of the porous Mo3 P/Mo nanobelt structure was disclosed by varying the contents of H2 /PH3 and the reaction temperature. During the hydrogen evolution reaction (HER) catalysis, the optimized porous Mo3 P/Mo nanobelts exhibited a small overpotential of 78 mV at a current density of 10 mA cm −2 and a low Tafel slope of 43 mV dec −1, as well as long‐term stability in alkaline media, surpassing Pt wire. Density functional theory (DFT) calculations reveal that the H2 O dissociation on the surface of Mo3 P is favorable during the HER.